Pan Icon Under Pressure - Unknown (Guardian)
Pan icon Bertie Marshall has been hospitalised at the Port-of-Spain General Hospital since he was having problems controlling his blood sugar level. Marshall is the inventor of the Bertfone, the double tenor and also credited with introducing canopies on pan.
Keywords: Inventors -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel drum (Musical instrument) -- Instruction and study -- Trinidad and Tobago